Innovation in Reading, Writing and Arithmetic Learning Based on VAKT for Moderate Mentally Retarded Students at SLB YPAC Makassar: Inovasi Pembelajaran Calistung Berbasis VAKT untuk Siswa Tunagrahita Sedang SLB YPAC Makassar - Dwi Julitha, Rasya Islami; Meyer, Ragil Prasetyo; Aolia, Nur Fadillah; Asran, Asran; Ramdanil, A.Dirga; Nasir, Munawir (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
SLB YPAC Makassar in South Sulawesi faces the challenge of a lack of educators, so some classes are combined, causing significant academic gaps. Deaf children at SLB YPAC Makassar also experience difficulties in learning Calistung and understanding abstract concepts. The proposed solution is the use of web-based VAKT (Visual, Auditory, Kinesthetic, Tactile) multisensory methods through the Robo Edu program. The implementation of the program is carried out using the Service Learning (SL) method which involves investigation, socialization, training, implementation, monitoring, reflection, and demonstration. Results showed a significant increase in students' Calistung skills by 85.54% from pre-test to post-test, as well as an increase in teacher skills by 62% based on questionnaire results. In conclusion, the implementation of the web-based VAKT method effectively improves the Calistung learning of students with disabilities and the teaching skills of teachers. Recommendations for the sustainability of the program are the formation of teacher cadres and cooperation with the Department of Education as well as support from the local government.